Território e serviço comunitário de saúde mental: as concepções presentes nos discursos dos atores do processo da reforma psiquiátrica brasileira Territory and community mental health service: conceptions present in the discourses of the actors of the process of Brazilian psychiatric reform - Adriana Leão; Sônia Barros (Universidade de São Paulo, 2012)
Uma das proposições dos Centros de Atenção Psicossocial (CAPS), serviços substitutivos de assistência à saúde mental de base comunitária e territorial, , é a intervenção no contexto de vida dos usuários, buscando explorar os recursos existentes para a viabilização dos projetos terapêuticos, os quais devem possibilitar transformações concretas no cotidiano. Nesse contexto, foi desenvolvida a pesquisa que tem como referencial metodológico a teoria da vida cotidiana, proposta por Agnes Heller, e as categorias analíticas, território e reabilitação psicossocial. Trata-se de um estudo de caso com a finalidade de identificar e discutir as possibilidades das práticas territoriais na produção de mudanças no cotidiano dos usuários. Nesse artigo, buscamos discutir um dos objetivos delineados no estudo: compreender a representação que a equipe multiprofissional tem sobre "território" e "serviço de saúde mental de base territorial". O campo do estudo constituiu-se em um dos CAPS III da cidade de Campinas/SP e os colaboradores desta pesquisa foram os trabalhadores de saúde mental, os usuários e não usuários do serviço. Os dados foram coletados por meio de entrevistas semiestruturadas e sessões de grupo focal. Na análise dos dados, sob o enfoque da Análise do Discurso, obteve-se como resultado o reconhecimento de três categorias empíricas, dentre as quais o território. As ações no território é que dão significado para o cotidiano do serviço e nisso reside a importância dessas intervenções, as quais diferenciam um hospital psiquiátrico de um serviço comunitário. One of the proposals of the territory- and community-based substitutive services in mental health assistance - the Centros de Atenção Psicossocial (CAPS - Psychosocial Care Centers) - is the intervention in the users' context, exploring existent resources to promote the feasibility of life projects, which in turn should enable concrete transformations in everyday life. The research was developed in this context and its methodological reference is the theory of everyday life proposed by Agnes Heller, and the analytical categories territory and Psychosocial Rehabilitation. It is a case study that intends to identify and discuss the possibilities of territorial practices in producing changes in the users' everyday life. In this article, one of the objectives outlined in the study is discussed: to comprehend the representation that the multiprofessional team has of "territory" and "territory-based mental health service". The field of the study was one of the CAPS III of the city of Campinas (State of São Paulo), and the collaborators of this research were the mental health professionals and the users and nonusers of the service. Data were collected by means of semi-structured interviews and focal group sessions. In the data analysis, under the perspective of Discourse Analysis, the result that was obtained was the recognition of three empirical categories, among them - territory. It is the actions in the territory that give meaning to the everyday life of the service, and in this resides the importance of these interventions, which differentiate a psychiatric hospital from a community service.